Node replication attacks in mobile wireless sensor network: a survey - Shaukat, Haafizah Rameeza; Hashim, Fazirulhisyam; Sali, Aduwati; Abdul Rasid, Mohd Fadlee (Hindawi Publishing Corporation, 2014)
Mobile wireless sensor networks (MWSNs) comprise a collection of mobile sensor nodes with confined and finite resources. They commonly operate in hostile environments such as battle fields and surveillance zones. Owing to their operating nature, MWSNs are often unattended and generally are not equipped with tamper-resistant tools. With little effort, an adversary may capture the nodes, analyze and replicate them, and surreptitiously insert these replicas at strategic locations within the network. Keeping in view of the above, this paper places an emphasis on this aforementioned attack, known as node replication attack in MWSNs. Specifically, the current state-of-the-art of node replication attack in MWSNs is discussed, where this paper provides a detailed description of various existing detection and prevention mechanisms in literature with an aim to provide better understanding of the factors that need to be considered when designing defence mechanism of node replication attack. A detailed categorization of various detection techniques is provided in the paper with critical discussion on each categorization with respect to its advantages, disadvantages, and various constraints. To conclude the paper, a number of parameters are selected for comparison and analysis of all the existing detection schemes in the literature.